The role of information resources in the use of e-Government - Sherzod, Pardayev (Журнал математики и информатики, 2022)
Abstract: Management of the system of training for small business and entrepreneurship in a market economy, thereby assessing the complexity and diversity of the relationship between the mechanism of training of these specialists, new scientifically based methodological approaches, the effectiveness of training, retraining and advanced training development of criteria, disclosure of the conceptual basis of the relationship between the quality of training of entrepreneurial personnel and the end results of their activities, as well as the identification of patterns of training and retraining for the business sector.